Potential Antibacterial Activity of Hydroxyapatite Composite And Green Betel Leaf Extract (Piper betle L.) Against Streptococcus mutans Bacteria - Lawarti, Riska Amelia; Cahyaningrum, Sari Edi (Indonesian Journal of Chemical Science, 2022)
Dental caries is a common oral disease and the main bacteria causing it is Streptococcus mutans. Hydroxyapatite is a material consisting of calcium and phosphate components that have dual abilities as remineralizing and antibacterial agents. In addition to hydroxyapatite, phenolic compounds and tannins in green betel leaf extract also have antimicrobial functions. Tannins and phenols act as poisons for microbes by inhibiting the enzyme activity of interfering microbes. The purpose of this study was to determine the physicochemical character and antibacterial activity of Streptococcus mutans from oral hydroxyapatite preparations and green betel leaf extract. In this study, hydroxyapatite and green betel leaf extract were used as oral preparations with variations in the addition of green betel leaf extract 0.1; 0.3; 0.5; 0.7 and 1 gram. The results of the FTIR analysis explain the absorption bands of the functional groups PO43-, OH and CO32- from hydroxyapatite, as well as the C=O and C-O groups from green betel leaf extract which have shifted the wave number, indicating that there has been a bond between hydroxyapatite and metabolite compounds in betel leaf extract. green. In PSA testing, the smallest particle size was indicated by the variation of hydroxyapatite composite and 0,3 gram green betel leaf extract, which was 690.08 nm. Testing the antibacterial activity of the hydroxyapatite-green betel leaf extract composite showed inhibitory activity against Streptococcus mutans bacteri.